Komunitní dům pro seniory – hrubá stavba - Pšikalová, Hana (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Cílem této práce je stavebně – technologické řešení hrubé stavby komunitního domu pro seniory v Benešově u Boskovic. Řešení objektu zahrnuje vypracování stavebně technologické zprávy, zařízení staveniště, technologických předpisů pro zdění a realizaci vodorovných monolitických konstrukcí, kontrolní a zkušební plán, řešení dopravních vztahů, návrh strojní sestavy, BOZP a environmentální plán. Dále je obsahem časový plán stavby a položkový rozpočet.

The aim of this thesis is the construction and technological solution of the rough construction of the community building for seniors in Benešov near Boskovice. The solution of the building includes the elaboration of building technology report, building equipment, technological regulations for masonry and realization of horizontal monolithic structures, control and test plan, solution of transport relations, design of machine assembly, health and safety and environmental plan. It also contains a building schedule and an item budget.
Community home for the elderly - Structural Work
Keywords: Objekt; stavba; staveniště; technologický předpis; BOZP; kontrolní a zkušební plán; strojní sestava; časový plán; rozpočet; zděné konstrukce; monolitické stropní konstrukce; environmentální plán.; Building; construction; construction site; technological regulativ; health and safety; inspection and test plan; working machinery; schedule; budget; brick structures; monolitic ceiling construction; protection of the enviroment